2019
DOI: 10.1130/l1124.1
|View full text |Cite
|
Sign up to set email alerts
|

Structural modeling of the Western Transverse Ranges: An imbricated thrust ramp architecture

Abstract: Active fold-and-thrust belts can potentially accommodate large-magnitude earthquakes, so understanding the structure in such regions has both societal and scientific importance. Recent studies have provided evidence for large earthquakes in the Western Transverse Ranges of California, USA. However, the diverse set of conflicting structural models for this region highlights the lack of understanding of the subsurface geometry of faults. A more robust structural model is required to assess the seismic hazard of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
42
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(50 citation statements)
references
References 45 publications
7
42
1
Order By: Relevance
“…This regional uplift rate is supported by research conducted for several master's theses set in the Santa Maria Basin that used fluvial or marine terraces to determine incision and uplift rates of ~1 mm/yr in the footwall blocks of the reverse faults (Kelty, 2020;Farris, 2017;Tyler, 2013). The cause of this regional uplift rate is beyond the scope of this study, but it is likely related to deeper crustal thickening, possibly along the detachment at 12-15 km depth that has been interpreted by multiple studies (Levy et al, 2019;Huang et al, 1996;Namson and Davis, 1990). Our rock uplift rates along the crests of the Casmalia Hills and Purisima Hills are likely superposed on this regional uplift, such that the rate of rock uplift due to the underlying blind faults modeled in this study are anywhere from near 0 mm/yr at the western nose of the Purisima Hills to a little less than 4 mm/yr in the eastern Purisima Hills.…”
mentioning
confidence: 80%
See 1 more Smart Citation
“…This regional uplift rate is supported by research conducted for several master's theses set in the Santa Maria Basin that used fluvial or marine terraces to determine incision and uplift rates of ~1 mm/yr in the footwall blocks of the reverse faults (Kelty, 2020;Farris, 2017;Tyler, 2013). The cause of this regional uplift rate is beyond the scope of this study, but it is likely related to deeper crustal thickening, possibly along the detachment at 12-15 km depth that has been interpreted by multiple studies (Levy et al, 2019;Huang et al, 1996;Namson and Davis, 1990). Our rock uplift rates along the crests of the Casmalia Hills and Purisima Hills are likely superposed on this regional uplift, such that the rate of rock uplift due to the underlying blind faults modeled in this study are anywhere from near 0 mm/yr at the western nose of the Purisima Hills to a little less than 4 mm/yr in the eastern Purisima Hills.…”
mentioning
confidence: 80%
“…Marshall et al (2013) measured an average geodetic shortening rate of 7 mm/yr, while other geodetic studies have reported rates as high as 12 mm/yr (Donnellan et al, 1993;Hagar et al, 1999). Measurements of geologic shortening rates since Miocene time vary from 6.5 to 9.1 mm/yr (Levy et al, 2019) to as high as 25 mm/yr (Yeats, 1983;Huftile and Yeats, 1995). Slip rates on faults in the western Transverse Ranges have mainly been determined in the Ventura area, where upper limits range from 7 to 11 mm/yr along the Ventura, San Cayetano, and Red Mountain faults (Fig.…”
Section: Implications For Regional Active Tectonicsmentioning
confidence: 99%
“…SPP = Santa Paula peak, SSCF = Southern San Cayetano fault, LMA = Lion Mountain anticline, JCF = Javon Canyon fault, LCF = Lion Canyon fault, WSCF = Western San Cayetano fault, ESCF = Eastern San Cayetano fault, SAF = San Andreas Fault, TC = Timber Canyon, OC = Orcutt Canyon, SPC = Santa Paula Creek. (Hubbard et al, 2014;Hughes et al, 2018;Levy et al, 2019;Namson & Davis, 1988;Nicholson, Sorlien, et al, 2017;Rockwell, 1988;Sorlien et al, 2000;Sorlien & Nicholson, 2015;Rockwell et al, 2016;Yeats et al, 1988).…”
Section: Background and Geological Settingmentioning
confidence: 99%
“…While modeled static Coulomb stress change on dip‐slip receiver faults is highly sensitive to changes in fault strike, dip‐slip faults also demonstrate sensitivity to changes in fault dip (Madden et al, 2013; Mildon et al, 2016; Mohammadi et al, 2019). Therefore, the ability to include down‐dip changes in fault dip is important, particularly in fold and thrust belts where faults are often interpreted to have ramp‐flat geometry (e.g., Hubbard et al, 2016; Levy et al, 2019; Shaw & Suppe, 1996; Suppe, 1983) and where ramp‐flat geometry can potentially control coseismic slip patterns (Hubbard et al, 2016). Furthermore, previous work has combined paleoseismic data and subsurface data with static Coulomb stress modeling to test feasible rupture scenarios between imbricate faults in the South Island, New Zealand (Stahl et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation